Specifying Standard Scores and Levels for Some Physical Variables as Indicators for Selecting Youth Soccer Players Aged (17 – 19) years Old - Alogaily, Ghassan Raheem; Amish, Saleh Radhi (Journal of Physical Education, 2021)
The importance of the study lies in specifying standard scores and levels for some physical variables based on special standardized scientific tests that help specialists and coaches select the best youth players in physical performance. The study aimed at identifying some physical variables for selecting youth soccer players as well as setting tests and standard scores and levels. The researchers used the descriptive method on (340) first-class youth players who represent (17) clubs. The researcher specified the physical variables and special tests for them then applied the tests to collect the data and come up with the conclusion and recommendations.